Local Wisdom Integration in Elementary Science Learning: Its Effect on Students’ Scientific Literacy - Daluti Delimanugari; Suyadi Suyadi; Ana Fitrotun Nisa; Ana Dwi Wahyuni; Mustolikh Khabibul Umam (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2026)
This study aims to analyse the effect of integrating local wisdom into science learning on improving elementary school students' scientific literacy. Students' scientific literacy in Indonesia is still low due to less contextual learning. The integration of local wisdom into science learning in elementary schools is also still limited and has not been widely explored. This study used a quantitative approach with a pre-experimental one-group pretest–posttest design. The subjects were 26 fifth-grade students of MI Nahdlatuth Thullab. The instrument was a scientific literacy test based on the OECD framework integrated with local contexts such as the Rasulan tradition and the Gunungkidul ecosystem. Data were analysed through validity, reliability, and N-Gain tests. The results showed the instrument was valid and reliable (α = 0.812). Local wisdom-based learning improved scientific literacy with an average N-Gain value of 0.32 (moderate category). These findings indicate that the integration of local wisdom can be a more meaningful and contextual learning alternative